PEMBERIAN ASI EKSLUSIF TERHADAP PERKEMBANGAN ANAK BERDASARKAN KPSP DI PUSKESMAS MANGASA MAKASSAR - Fitriati Sabur; Afriani Afriani (Sekolah Tinggi Pariwisata Mataram, 2021)
Breast milk is the best and most nutritious food for babies. Exclusive breastfeeding for the first 6 months, without additional food or drink is very important in the process of growth and development of babies such as increasing weight & weight. This basic growth will influence and determine the next child's development. The purpose of this study was to determine the effectiveness of exclusive breastfeeding for infants in monitoring the development of children aged 6-24 months in the Mangasa Health Center area of ​​Makassar City. This type of observational analytic research with a cross sectional approach, the population of mothers under five as many as 397 people, the sampling technique was purposive sampling as many as 30 people. The research data was tested using chi square. The results showed that there was an effect of the effectiveness of exclusive breastfeeding on child development using KPSP in the Mangasa Health Center Makassar City with a p value of 0.06. It is expected that the role of midwives is related to exclusive breastfeeding for child development by using KPSP in the work area of ​​the Mangasa Health Center Makassar City in 2021